Therapeutic effect and rebound evaluation of dapagliflozin on glycated hemoglobin (HbA1c) in type 1 diabetes mellitus patients - Wang, Dong-Dong; Zhang, Cun; Hu, Ke; He, Su-Mei; Zhu, Ping; Chen, Xiao (Frontiers in Pharmacology, 2023)
Dapagliflozin has been used to treat patients with type 1 diabetes mellitus (T1DM), however the actual drug efficacy of dapagliflozin on glycated hemoglobin (HbA1c) and whether there is a rebound from dapagliflozin efficacy on HbA1c remain unknown. The present study aimed to explore the actual therapeutic effect and rebound situation of dapagliflozin on HbA1c in T1DM patients. Two 5 mg/day dapagliflozin dosage groups and three 10 mg/day dapagliflozin dosage groups, a total 1594 T1DM patients were collected for analysis with a non-linear mixed effect model. The change rate of HbA1c from baseline value was chosen as dapagliflozin pharmacodynamic evaluation index. After deducting control group effects, 5 and 10 mg/day dapagliflozin on HbA1c in T1DM were no significant difference. In addition, the actual maximal efficacy (AEmax) of dapagliflozin on HbA1c was -6.24% at week 9. When it reached the AEmax, the dapagliflozin pharmacodynamic rebound on HbA1c occurred, and continuing treatment for 0.5 and 1 years, the actual efficacies were -4.70% (75% AEmax) and -3.27% (52% AEmax), respectively. It was the first time to clarify the actual therapeutic effect and rebound situation of dapagliflozin on HbA1c in T1DM patients, providing reference value for clinical practice.